2006
DOI: 10.1021/ja058217m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pd Nanoparticle Size on the Catalytic Hydrogenation of Allyl Alcohol

Abstract: We report that the rate of hydrogenation of allyl alcohol is a function of the diameter of the Pd nanoparticles (1.3-1.9 nm) used to catalyze the reaction. Furthermore, kinetic data indicate that this effect is electronic in nature for particles having diameters <1.5 nm, but for larger particles it depends primarily on their geometric properties. This is a significant finding, because it represents a particle size effect for hydrogenation over unsupported Pd nanoparticle catalysts in a size range that has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
296
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(303 citation statements)
references
References 20 publications
7
296
0
Order By: Relevance
“…Dendrimer templates have been also used to exert a high degree of control over the size of catalytically active nanoparticles in the ,3 nm range (51,52). Specifically, sixth-generation, hydroxyl-terminated polyamidoamine Nanocatalysis with Controlled Shape and Size dendrimers (G6-OH) at different Pd/dendrimer ratio were used to produce Pd nanoparticles of 1.3 ¡ 0.3, 1.4 ¡ 0.3, 1.5 ¡ 0.4, 1.7 ¡ 0.3, and 1.9 ¡ 0.2 nm.…”
Section: Dendrimeric Stabilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimer templates have been also used to exert a high degree of control over the size of catalytically active nanoparticles in the ,3 nm range (51,52). Specifically, sixth-generation, hydroxyl-terminated polyamidoamine Nanocatalysis with Controlled Shape and Size dendrimers (G6-OH) at different Pd/dendrimer ratio were used to produce Pd nanoparticles of 1.3 ¡ 0.3, 1.4 ¡ 0.3, 1.5 ¡ 0.4, 1.7 ¡ 0.3, and 1.9 ¡ 0.2 nm.…”
Section: Dendrimeric Stabilizersmentioning
confidence: 99%
“…The advances in colloidal preparation of metal nanostructures open new opportunities in the study of structure-sensitive catalytic reactions (6,24,51). Nanostructures of various shapes and sizes have become a powerful tool in revealing the reaction active sites due to a predominance of definite surface atoms on some nanostructures.…”
Section: Nanocatalysis With Controlled Shape and Sizementioning
confidence: 99%
“…As discussed in the introduction, alcohols are often used as solvents in reactions catalyzed by Pdbased catalysts [33], or they may be used even as reactants [34][35][36][37][38][39][40][41]. Therefore, it is important to clarify if they are innocent toward the catalyst, or if they may react with it and eventually lead to its final deactivation.…”
Section: Thermal Behavior Of P4vp/pd(oac)2 In Presence Of Alcohols: Imentioning
confidence: 99%
“…In other cases, alcohols are used as reactants. For example, alcohol hydrogenation, oxidation and cross-coupling reactions are also catalyzed by palladium-based catalysts, either homogeneous or heterogeneous [34][35][36][37][38][39][40][41]. In this respect, the homogeneous Pd(OAc)2/pyridine system is by far one of the most efficient and selective catalyst for oxidation of alcohols to aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggested that highly dispersed Pd nanoparticles are extraordinarily active and may exhibit unique properties in a wide range of important chemical processes [2,14,15]. Various strategies were developed for incorporating metal nanoparticles into mesoporous silica, which could be generally classified into three groups: (1) chemical vapor deposition of metal precursors into the silica frameworks [16,17]; (2) wet impregnation or ion exchange of the appropriate metal salt into the host silica, followed by thermal treatment and reduction procedure [18,19]; and (3) synthesis of the mesoporous materials around the pre-prepared metal nanocrystals [20].…”
Section: Introductionmentioning
confidence: 99%